(untitled) (Research, Society and Development, 2022)
The study aims to analyze the scientific production on technologies for mental health care used and/or produced with the contribution of nursing. This is an integrative review carried out from December 2021 to March 2022. The search took place in the LILACS, SCIELO, MEDLINE/Pubmed and SCOPUS databases. The guiding question established was: which health technologies are used and/or produced with the contribution of nursing to mental health care? The following descriptors were used for the crossing: nursing, Biomedical Technology, technology, mental health and mental disorders, using the Boolean operator “AND” between them. We identified 6841 studies that were submitted to the established inclusion and exclusion criteria. It resulted in a total of 16 articles. The results showed a greater number of studies that involved hard technologies, such as mobile applications, health robots, online programs and artificial intelligence. The reception and musical intervention were identified as light technological devices; and how hard technologies are scales in health and the nursing process. The use of technological devices was detected in different scenarios, such as in primary care, specialized services, long-stay institutions, home care agencies, universities, which involved different audiences such as elderly people with dementia, adolescents with anxiety, university students and caregivers of individuals. with mental disorders. It was noticed that these technologies were effective and provided positive results.